Answer:
- (x - 3y)(3x + y)
Step-by-step explanation:
Given
(x + 2y)² - (2x - y)² ← expand both parenthesis using FOIL
= x² + 4xy + 4y² - (4x² - 4xy + y²) ← distribute
= x² + 4xy + 4y² - 4x² + 4xy - y² ← collect like terms
= - 3x² + 8xy + 3y² ← factor out - 1 from each term
= - 1(3x² - 8xy - 3y²) ← factor the quadratic
Consider the factors of the product of the coefficient of the x² term and the coefficient of the y² term which sum to give the coefficient of the xy- term.
product = 3 × - 3 = - 9 and sum = - 8
The factors are - 9 and + 1
Use these factors to split the xy- term
3x² - 9xy + xy - 3y² ( factor the first/second and third/fourth terms )
= 3x(x - 3y) + y(x - 3y) ← factor out (x - 3y) from each term
= (x - 3y)(3x + y)
Thus
(x + 2y)² - (2x - y)² = - (x - 3y)(3x + y)
F = 1.8C + 32
С = -10 ⇒ F = 1.8·(-10) + 32 = 14 ⇒
(-10, 14)С = 0 ⇒ F = 1.8·(0) + 32 = 32 ⇒
(0, 32)
С = 10 ⇒ F = 1.8·(10) + 32 = 50 ⇒
(10, 50)С = 20 ⇒ F = 1.8·(20) + 32 = 68 ⇒
(20, 68)
Y=mx+b
m=slope
b=yintercept
given
slope=-1/4
yint=5
y=-1/4x+5
4 1/5 should be your answer
Step-by-step explanation:
c=5/9(f-32) can also be written as c = 5(f - 32)/9.
Multiply each side by 9.
That gives us 9c = 5(f - 32).
Apply distributive rule on the right side.
9c = 5f - 160
Add 160 to the left side.
9c + 160 = 5f
Lastly, divide both sides 5.
(9c + 160)/5 = f